The Influence of Ne Bis In Idem on Inheritance - Paulus Tiku Taru Padang (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze and explain the influence ne bis in idem on inheritance. The method used in this study is a normative legal research method with primary legal materials. The results of the study show that in the second case/dispute the Makale District Court Decision Number: 103/Pdt.G/2015/PN. Mkl., contrary to the principle ne bis in idem, because the judge only considered that the subject of the case was the same and the object of the case was the same, so this case entered ne bis in idem without assessing the legal relationship between Defendant I and Defendant II. Defendant II redeems the pawn object from Defendant I but between Defendant II and Defendant I has never entered into a pawn agreement so that Defendant II does not have the right to redeem the pawn object/object of dispute. To avoid the confusion mentioned above, in this third case, if G. Yohana Lembang wants to fight for his right to obtain the distribution of inheritance from his deceased parents, then G. Yohana Lembang must change his position as Defendant II and the Plaintiff is his 2 brothers who have not been involved in the first and second cases and the object of the dispute is changed to undivided inherited land. So the influence ne bis in idem on inheritance does not exist. so that G. Yohana Lembang can obtain his rights through the distribution of inheritance that has not been divided.